2020
DOI: 10.1177/2333794x20974218
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tube Defects and Associated Factors among Neonates Admitted to the Neonatal Intensive Care Units in Hiwot Fana Specialized University Hospital, Harar, Ethiopia

Abstract: Background: Neural tube defects are a major public health problem and substantially contribute to morbidity and mortality, particularly in low-income countries, including Ethiopia. There are a paucity of data on the magnitude and associated factors of neural tube defects in Ethiopia, particularly in the study setting. Objective: This study aimed to assess the magnitude of neural tube defects and associated factors among neonates admitted to the neonatal intensive care unit in Hiwot Fana Specialized University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(78 reference statements)
2
3
0
Order By: Relevance
“…Spina bifida accounted for the majority (77.8%) of cases, and anencephaly and encephalocele accounted for 11.1% each. This is comparable to the study done at NICU in HFSUH Eastern Ethiopia having a prevalence of 5.71%; of these, 20 (83.5%) and 4 (16.5%) had spina bifida and encephalocele respectively ( 18 ). NTDs were defined as cases of anencephaly, spina bifida, and encephalocele based on ICD-10 criteria.…”
Section: Discussionsupporting
confidence: 83%
“…Spina bifida accounted for the majority (77.8%) of cases, and anencephaly and encephalocele accounted for 11.1% each. This is comparable to the study done at NICU in HFSUH Eastern Ethiopia having a prevalence of 5.71%; of these, 20 (83.5%) and 4 (16.5%) had spina bifida and encephalocele respectively ( 18 ). NTDs were defined as cases of anencephaly, spina bifida, and encephalocele based on ICD-10 criteria.…”
Section: Discussionsupporting
confidence: 83%
“…With respect to the geographical coverage of studies, a total of eight studies were cross-regional studies (studies taken in two or more regions of the country), among them three studies took place in Addis Ababa and Amhara region simultaneously,59–61 four studies were conducted in east part of county including Oromia, Harari, Somalia and Dire Dawa city administration62–65 and one study was carried out in Sidama and Southern Ethiopia region 66. On the other hand, the remaining studies were exclusively conducted in four regions and one city administration (Addis Ababa=5,67–71 Amhara=13,72–84 Harari=1,85 Oromia=1086–95 and Tigray=596–100). As displayed in the annex section, online supplemental table 3, a total of 611 064 participants were involved in 42 studies.…”
Section: Resultsmentioning
confidence: 99%
“…A structured questionnaire that had been utilized in Ethiopia before [ 32 , 38 , 39 ] was employed in this investigation. The questionnaire was prepared in English first, then translated into local languages (Afan Oromo, Amharic, and AF Somali), and then back to English by language experts to ensure consistency.…”
Section: Methodsmentioning
confidence: 99%
“…NTD research is uncommon in Ethiopia, particularly in the eastern region. The burden of NTDs was 5.71% among neonates admitted to the neonatal intensive care unit at Hiwot Fana Specialized Hospital (HFCSH) in Harar in a cross-sectional study of NTDs and associated factors [ 32 ]. A retrospective cohort study of neonates born in three referral hospitals in Ethiopia revealed an unacceptably high rate of NTDs, 107.5 per 10,000 live births, which was five times higher than the WHO estimate for Ethiopia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%